(untitled) (Revista Brasileira de Iniciação Científica, 2025)
The aim of this article is to study security options that promote the protection of women in public areas of smart cities. The research was based on a systematic literature review, in which articles were analyzed in two databases between May and June 2024. After the review, six studies were considered: two of them present proposals using software, three highlight the importance of smart urban design and one study discusses the application of intelligent systems. Six relevant studies were analyzed, showing that the combination of inclusive urban design and intelligent security systems, such as mobile apps and integrated surveillance, can improve public safety and women’s perception of safety.